Assessing The Core Capacity, Working Practice Capacity Of Local Civil Servants In Vietnam (Journal of Namibian Studies : History Politics Culture, 2023)
n state agencies, civil servants enforce laws and policies according to their areas of expertise to manage social development. The issue of the quality of civil servants is often clearly defined by the laws of the countries, reflected in both their qualifications and their capacity. Many studies also mentioned and analyzed the quality (core competencies) and practical working capacity when assessing the quality of civil servants. In this study, on the basis of inheriting many previous studies and applying the issued legal regulations of Vietnam, the author surveys and evaluates the quality of local civil servants in Vietnam in two areas: Core competencies and practical working capacity of civil servants. The author builds a theoretical framework and directly surveys 270 leaders of communal government agencies in 3 localities representing 3 regions of Vietnam, including: Thai Nguyen province (Northern region), Quang Ngai province (Central region), Tay Ninh province (Southern region). Research results show that local leaders underestimate the practical capacity of civil servants. From the conclusion of this study, the author suggests some contents that need to be researched and adjusted in Vietnam's local government policy on civil servant management.